The Right to Fair Compensation and Transparency in Land Acquisition, Rehabilitation and Resettlement Act, 2013 - Bare Act (Delhi Professional Book Publishers, 2023)
School of Law, Governance and Public Policy
MIR No:318
Keywords: Property Law